Electrosynthesis of hydrogen peroxide using modified gas diffusion electrodes (MGDE) for environmental applications: Quinones and azo compounds employed as redox modifiers - Moreira, Juliana; Bocalon Lima, Verônica; Athie Goulart, Lorena; Lanza, Marcos R.V. [UNESP] (Elsevier, 2019)
Although the electrosynthesis of hydrogen peroxide (H2O2) using gas diffusion electrodes (GDE) is a viable option for the production of this oxidizing agent in advanced oxidation processes (AOP) for wastewater treatment, the quest for more efficient electrodes is still regarded a matter of great importance in this area. The present study sought to investigate different redox organic compounds employed as modifiers of carbon black Printex L6 (CP) with the aim of increasing H2O2 production using carbon-based electrodes. Varying amounts of the modifiers, including Sudan Red 7B (SR7B), methyl-p-benzoquinone (MPB), anthraflavic acid (AA) and anthraquinone-2-carboxylic acid (A2CA), were added to carbon black, where the electrochemical activity was studied by applying a microporous catalyst layer on a rotating ring-disk electrode (RRDE). The materials containing 0.5% of SR7B and 5.0% of MPB increased the current efficiency for the electrogeneration of hydrogen peroxide to 86.2% and 85.5%, respectively, compared to 82.8% obtained for unmodified carbon. Carbon Printex L6 gas diffusion electrodes modified with 0.5% of SR7B were studied and the following results were obtained: the application of current density of 75 mA cm−2 led to the production of 1020.1 mg L-1 of H2O2, with an energy consumption of 118.0 kW h kg-1, apparent kinetic constant of 37.34 mg L-1 min-1 and current efficiency of 17.87%. Conversely, the use of GDE with unmodified carbon resulted in the production of relatively less quantity of H2O2 which amounted to 717.3 mg L-1, with more energy consumption of 168.5 kW h kg-1, lower apparent kinetic constant of 21.41 mg L-1 min-1 and lower current efficiency of 12.57%. Based on these results, carbon Printex L6 GDE modified with 0.5% of Sudan Red 7B is seen as a suitable alternative for the production of high amounts of H2O2 which can be applied in advanced oxidation processes in acidic medium.
Keywords: Carbon black -based electrodes; Electrosynthesis of hydrogen peroxide; Gas diffusion electrode; Oxygen reduction reaction; Redox organic compounds modifiers